Understanding HMF inhibition on yeast growth coupled with ethanol production for the improvement of bio-based industrial processes. (October 2022) - Gencturk, Elif; Ulgen, Kutlu O.
Abstract: Inhibitory compounds generated from biomass hydrolysis affect the production of biofuels. HMF is a furan derivative inhibitor and influences the ethanol yield by inhibiting enzymes such as alcohol dehydrogenase, aldehyde dehydrogenase and glycolysis. The most striking effect of HMF on the organisms is that it interferes with the microbial growth and is considered as the most potent inhibitor in bioethanol production. In this study, HMF inhibition within yeast cells is investigated by both computational (COBRA) and experimental approaches. The active subsystems in the medium with and without HMF and the coupling types of the reactions are determined to get an insight on how to improve bioethanol production by strain engineering techniques. While extracellular transport subsystem is prominent in term of flexibility, post transcriptional regulation is outstanding among transcriptional to metabolic regulation types. The strategies to increase biomass and ethanol simultaneously with gene/reaction deletion methods are discussed, and ethanol production can be increased by 17% up to 33.35 mmol gDW −1 hr −1 with several reaction deletions. The genome scale metabolic model and the complementary experiment given here shed light on the biofuel management in the bio-based industry for future. Graphical Abstract: ga1 Highlights: HMF decreased the biomass generation and ethanol production rate Biomass generation and ethanol production have highest flexibility in extracellular transport and sterol metabolisms Post transcriptional regulation is the most dominant type of regulation in GSM model Ethanol production is increased from 28.43 mmol gDW −1 h −1 to 33.35 mmol gDW −1 h −1 by various gene/reaction deletions Metabolic network regulated can eliminate toxic by-products and overproduce chemical compounds of interest